2016
DOI: 10.1016/j.catena.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of precipitation and restoration vegetation on soil erosion in a semi-arid environment in the Loess Plateau, China

Abstract: a b s t r a c t a r t i c l e i n f oSoil erosion is a critical environmental problem of the Loess Plateau, China. As an important project for soil and water conservation in the semi-arid environment, the Grain-for-Green extensively transformed a wide range of farmland into vegetated land after the 1980s. Yet, the effects of vegetation restoration on soil erosion reduction are not well understood. In this study, we monitored runoff and sediment yield at sites restored with six typical restoration vegetation ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
118
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(127 citation statements)
references
References 54 publications
4
118
0
5
Order By: Relevance
“…The group 3 had greater precipitation depth (162 mm) and erosivity (2869 MJ mm ha -1 h -1 ) showing a possible direct relationship between these two variables (Table 3). Zhou et al (2016) assessed the relationship between precipitation and hydro-sedimentological processes and found the I30 as the determining factor for the formation of similar groups of events with SP. Different than the other two managements, the events that produced more sediments in the DC were grouped in group 2 (Figure 6), since a single event of this group produced 1298.7 kg ha -1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The group 3 had greater precipitation depth (162 mm) and erosivity (2869 MJ mm ha -1 h -1 ) showing a possible direct relationship between these two variables (Table 3). Zhou et al (2016) assessed the relationship between precipitation and hydro-sedimentological processes and found the I30 as the determining factor for the formation of similar groups of events with SP. Different than the other two managements, the events that produced more sediments in the DC were grouped in group 2 (Figure 6), since a single event of this group produced 1298.7 kg ha -1 .…”
Section: Resultsmentioning
confidence: 99%
“…The information on the precipitation characteristics and vegetation distribution in a semiarid environment are the basis to prevent of soil loss (ZHOU et al, 2016). Vegetation management can significantly decrease water infiltration rates and increase surface runoff and erosion (SANTOS, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these precipitations had the highest I 30 (maximum intensity of precipitation in thirty minutes). Zhou et al (2016) assessed the influence of rain on soil loss and found that the determining factor for the formation of erosive groups was the I 30 . Wester et al (2014) also studied the interaction of these factors and pointed the soil exposure as a major factor for sediment transport in areas that had a burning procedure.…”
Section: Resultsmentioning
confidence: 99%
“…The sensors were calibrated, since they measure the frequency by an equation (potential frequency / height of the water column) (Figure 2a), to measure the surface runoff height, with data acquired every five minutes (RODRIGUES et al, 2013a). The surface runoff was determined by Equation 1, following the procedure used by Fang et al (2012), Rodrigues et al (2013b) and Zhou et al (2016). (1 Where: Q is the Parshall flume flow (L s -1 ); W is the width of the flume bottleneck (cm), with value of 47.5 for FC and TC and 30 for the DBP flume; and h is the height of the water in the flume (cm).…”
Section: Methodsmentioning
confidence: 99%
“…O conhecimento da intensidade das chuvas em um ambiente semiárido está entre os principais componentes para a prevenção da perda de solo (AMARAL et al, 2014;ZHOU et al, 2016).…”
Section: Introductionunclassified